Reliability and validity of the PL-C Quest, a scale designed to assess children's self-reported physical literacy. (May 2022) - Barnett, Lisa M.; Mazzoli, Emiliano; Bowe, Steven J.; Lander, Natalie; Salmon, Jo
Abstract: Background: The Physical Literacy in Children Questionnaire (PL-C Quest) was developed to assess children's perceived physical literacy. Pictorial items assess 30 elements within four domains (Physical - 12 items, Psychological - 7 items, Social - 4 items and Cognitive - 7 items). The aim of this study was to assess the reliability and construct validity of the PL-C Quest in Australian children aged 7–12 years. Methods: In 2020, Australian parents and children were recruited via social media (Sample 1: n = 80) and panel sampling (Sample 2: n = 589). Parents consented online, completed demographic details and children completed the PL-C Quest online. Test-retest reliability was assessed in a sub-group of Sample 1 (n = 59). Internal consistency and construct validity [Structural Equation Modelling (SEM)] were assessed using combined samples. A Confirmatory Factor Analysis (CFA) SEM was tested based on the hypothesized structure of four subdomains and a higher order factor of physical literacy. Results: Most parents were born in Australia (78%) and had a university education [University (61%), Trade (16%), High school (15%) and less than High school (8%)]. Children (59% boys; 40% girls; 1% other) had a mean age of 10.1 years (SD = 1.7). Physical literacy did not differ by age, but children of tertiary educated parents had higher physical literacy levels. Test-retest values (Mean = 15.8 days apart) were adequate to good [overall: ICC = 0.83, physical: ICC = 0.80, psychological: ICC = 0.76, social: ICC = 0.66, cognitive: ICC = 0.75]. Internal consistency values were as follows: overall: α = 0.92; physical: α = 0.82; psychological: α = 0.75; social: α = 0.72; cognitive: α = 0.77. All items except two loaded on sub-domains above 0.45. The final model had an adequate fit (SRMR = 0.043, CFI = 0.92, TLI = 0.90, RMSEA = 0.045). Conclusions: Results indicate the PL-C Quest has acceptable test-retest reliability and construct validity. Further research could seek to explore validity in children aged 5 and 6 years of age and in other cultural contexts. Highlights: The PL-C Quest assesses children's self-perceived physical literacy holistically. The main cartoon character is not male or female, nor from a particular ethnicity. Reliability values were good. The final hypothesized model had an adequate fit. The PL-C Quest can be used to assess children's perceived physical literacy.